Patterns of High-Alert Medicine Use in Geriatric Patients at Rumah Sakit Umum Pusat Dr. Cipto Mangunkusumo - Malihi, La; Supadmi, Woro; Trisna, Yuliana; Purwanto, Barkah Djaka (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Geriatric patients are patients who are often associated with multiple diseases and decreased organ function so they are at greater risk of developing unwanted drug reactions due to drug use when compared to other adults. High Alert Medication (HAM) are drugs that have a high risk of causing significant harm to patients if used incorrectly.Objectives: This study aims to determine the pattern of HAM use among inpatient geriatric patients at Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo Jakarta.Methods: Retrospective cohort study by reviewing primary data from medical records (MR) of inpatient geriatric patients who used HAM for the period January 1 to December 31, 2023. The sample consisted of 300 geriatric patients who met the inclusion criteria using a purposive sampling technique. Descriptive data analysis includes data in the form of frequencies and percentages (%).Results: Based on gender, women with a total of 162 (54%) patients dominated. Based on age, the age range of 60 to 70 years with a total of 104 (68.87%) patients with a diagnosis of hypertension dominated compared to other ages. Based on the type of HAM used namely Insulin group HAM with 53 (20.38%) times of administration with the type of insulin in the form of novorapid flexpen 3 ml (13,532%) and anticoagulant group HAM with 49 (18,84%) times of administration with the type of anticoagulant in the form of heparin sodium 5 ml (13,181%) with the diagnosis of hypertension.Conclusion: The types of HAM that dominate the use in the therapy of hospitalized geriatric patients are novorapid flexpen 3 ml and heparin sodium 5 ml given parenterally with a diagnosis of hypertension.